Spatial Distribution of Heavy Metals in the Surface Sediments of the Southern Coast of Pacitan, Indonesia - Defri Yona; Mochamad Arif Zainul Fuad; Nurin Hidayati (Indonesian Journal of Chemistry, 2018)
This study was conducted to analyze the spatial distribution of heavy metals from four different coastal areas in southern Pacitan, Indonesia: Pantai Watu Karung (WK), Pantai Teleng Ria (TL), Pantai Pancer (TP) dan Pantai Soge (SG). Data collected in this study included: temperature, salinity, DO, pH, sediment, organic matter and heavy metals in the sediments (Pb, Hg and Cd). The results showed different distribution patterns of heavy metals. Heavy metal concentrations, especially Pb and Hg, were found to be higher in Pantai Soge, while the concentration of Cd was higher in Pantai Pancer. An ANOVA test showed the distributions of Pb and Cd were significantly different (p < 0.01) between sampling sites. Variability of the physicochemical parameters influenced the variabilities of heavy metal concentrations among sampling sites. Overall, heavy metal concentrations in the study areas are rather low; however, attention is still needed due to heavy activities in the coastal areas of southern Pacitan that can contribute to heavy metal pollution.